2005
DOI: 10.1007/s00296-005-0599-5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelıal dysfunctıon ın patıents wıth prımary Sjögren’s syndrome

Abstract: The aim of this study was to determine the endothelial function in patients with primary Sjögren's syndrome (SS). We also aimed to determine whether endothelial (dys)function correlates with extraglandular manifestations, specific autoantibodies and the severity of salivary gland involvement of SS. Endothelium-dependent vasodilation and endothelium-independent vasodilation of the brachial artery were assessed by a high-resolution ultrasound on 25 patients with primary SS and on 29 healthy controls. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 15 publications
0
20
1
Order By: Relevance
“…Compared to patients with CV disease risk factors, circulating anti-SSA/Ro and anti-SSB/La antibodies (P ≤ 0.001 and P ≤ 0.04, respectively), leucopenia (P ≤ 0.02), hypergammaglobulinaemia (P ≤ 0.001) and hypocomplementaemia (P ≤ 0.001) were more common in patients without any CV disease risk factors. Based on these findings and the previous demonstration that anti-SSA/SSB antibodies and leucopenia are associated with subclinical ATS in patients with pSS [14,15], we investigated the possible relationship between these laboratory characteristics of pSS and CV disease risk factors in the entire cohort. Patients with evidence of circulating anti-SSA/SSB antibodies were characterized by a higher frequency of parotid enlargement (P ≤ 0.0001), purpura (P ≤ 0.005), extra-glandular involvement (P ≤ 0.0001), lymphoma (P ≤ 0.02), hypergammaglobulinaemia, rheumatoid factor positivity, leucopenia (P ≤ 0.0001 for all) and use of HCQ (P ≤ 0.005) and IS therapies (P ≤ 0.03).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared to patients with CV disease risk factors, circulating anti-SSA/Ro and anti-SSB/La antibodies (P ≤ 0.001 and P ≤ 0.04, respectively), leucopenia (P ≤ 0.02), hypergammaglobulinaemia (P ≤ 0.001) and hypocomplementaemia (P ≤ 0.001) were more common in patients without any CV disease risk factors. Based on these findings and the previous demonstration that anti-SSA/SSB antibodies and leucopenia are associated with subclinical ATS in patients with pSS [14,15], we investigated the possible relationship between these laboratory characteristics of pSS and CV disease risk factors in the entire cohort. Patients with evidence of circulating anti-SSA/SSB antibodies were characterized by a higher frequency of parotid enlargement (P ≤ 0.0001), purpura (P ≤ 0.005), extra-glandular involvement (P ≤ 0.0001), lymphoma (P ≤ 0.02), hypergammaglobulinaemia, rheumatoid factor positivity, leucopenia (P ≤ 0.0001 for all) and use of HCQ (P ≤ 0.005) and IS therapies (P ≤ 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…Although patients with pSS show signs of precocious subclinical ATS [12,16], conclusive evidence of increased CV events or deaths in these patients is currently lacking. In addition, the prevalence and role of traditional CV disease risk factors and their interaction with disease-related features of this systemic autoimmune disorder have not been fully investigated [12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with our findings, the majority of the studies have observed an excess of atherosclerosis, despite using different methods. Therefore, endothelial dysfunction (11)(12)(13)(14), increased arterial stiffness (11), increased carotid intima-media thickening (CIMT) (9), and abnormal ankle brachial index (15) have been more or less consistently described in these patients. There is only one study in particular that to our knowledge has investigated PWV in primary SS.…”
Section: Discussionmentioning
confidence: 99%